Systemic effects of BMP2 treatment of fractures on non-injured skeletal sites during spaceflight - Zamarioli, Ariane; Adam, Gremah; Maupin, Kevin A.; Childress, Paul J.; Brinker, Alexander; Ximenez, Joao P. B.; Chakraborty, Nabarun; Gautam, Aarti; Hammamieh, Rasha; Kacena, Melissa A. (Frontiers in Endocrinology, 2022)
Unloading associated with spaceflight results in bone loss and increased fracture risk. Bone morphogenetic protein 2 (BMP2) is known to enhance bone formation, in part, through molecular pathways associated with mechanical loading; however, the effects of BMP2 during spaceflight remain unclear. Here, we investigated the systemic effects of BMP2 on mice sustaining a femoral fracture followed by housing in spaceflight (International Space Station or ISS) or on Earth. We hypothesized that in spaceflight the systemic effects of BMP2 on weight-bearing bones would be blunted compared to that observed on Earth. Nine-week-old male mice were divided into 4 groups: (1) Saline+Earth; (2) BMP+Earth; (3) Saline+ISS; and (4) BMP+ISS (n=10 mice/group, but only n=5 mice/group were reserved for micro-computed tomography analyses). All mice underwent a femoral defect surgery and were followed for approximately 4 weeks. We found a significant reduction in trabecular separation within the lumbar vertebrae after administering BMP2 at the fracture site for mice housed on Earth. In contrast, BMP2 treatment led to a significant increase in trabecular separation, concomitant with a reduction in trabecular number within spaceflown tibias. Although these and other lines of evidence support our hypothesis, the small sample size associated with rodent spaceflight studies limits interpretations. That said, it appears that a locally applied, single dose of BMP2 at the femoral fracture site can have a systemic impact on distal bones, affecting bone quantity in several skeletal sites. Moreover, our results suggest that BMP2 treatment works through a pathway involving mechanical loading, in which the best outcomes during its treatment on Earth occurred in the weight-bearing bones and in spaceflight occurred in bones subjected to higher muscle contraction.